STUDENT PERCEPTIONS OF BASIC SKILLS PROGRAM STUDENT TEACHING PRACTICE FIELD (PPL) STKIP PGRI WEST SUMATRA EVEN SEMESTER ACADEMIC YEAR 2013/2014 IN CLASS VII SMP N 22 PADANG - Putri, Reni Eka (Pendidikan Ekonomi, 2014)
The purpose of this study was to determine the perception of the seventh grade students of SMP N 22Champaign to teach students the basic skills of field practice program (PPL) STKIP PGRI West SumatraSemester Academic Year 2013/2014.This research uses a quantitative approach. The study population is the entire seventh grade students ofSMP N 22 Padang 2013/2014 academic year consisting of 254 people and sampling techniques in this studyusing simple random sampling technique so that the sample in this study were as many as 155 people.Collecting data in this study using a questionnaire of 32 items. The data obtained were analyzed usingpercentage calculations.From the results of this research is that teachers skills in teaching at PPL SMP N 22 Padang in terms ofskills is quite open lesson with TCR 78.84%. Students perceptions of teachers teaching basic skills in managinga class PPL is quite the TCR 78.86%. Students perceptions about the teaching of basic skills in connection withexplaining the fairly with TCR 77.81%. Students perceptions of teachers skills in teaching PPL held inconnection with the variation is quite the TCR 75.59%. Students perceptions of teachers skills in teaching withrespect to PPL asking quite enough to TCR 74.45%. Teachers skills in teaching at PPL SMP N 22 Padang inconnection with providing reinforcement is quite the TCR 74.16%. Perceptions of students in relation to theteaching of basic skills related teacher closes the lesson is quite the TCR 74.32%. Based on the research resultssuggested to PPL students to improve basic skills of teaching and provide reinforcement in connection withproviding the opportunity for students to express opinions and closing skills related lesson provides a glimpse ofinformation about the matter to the next meeting, before the clock expires lessons.